Pluralidade familiar no Brasil e a legitimação jurídica conquistada com a Constituição de 1988: Family plurality in Brazil and legal legitimation achieved with the Constitution of 1988 - Sales, Cyntia Mirella Cangussu Fernandes (2023)
The way people organize themselves into families changes in line with the society in which they are based. In Brazil, transformations in family organization are evidenced by several factors and have motivated changes in the social and legal conception of this social organism. Aware of social changes, the 1988 Constitution of the Federative Republic of Brazil recognized as a family entity different models of forming a family, which eliminated the exclusivity of marriage established in Brazilian legislation. This recognition enabled the conquest of rights by several family arrangements that were previously relegated to invisibility by the national legal system. Thus, the present study aims to present a brief description of the main legal aspects contributed to the different types of family arrangements in contemporary Brazil, starting with a delimitation of the general aspects of the legal recognition of the plural family in the country, to then address the models family that has gained relevance in the legal system and the conquest of rights by each of these forms of family organization. For this purpose, the work is based on bibliographic research, which uses Brazilian legislation as well as legal literature and judicial decisions.